Complex fracture description and quasi-elastic energy development mathematical model for shale oil reservoirs - Rui, Wang; Zhengdong, Lei; Han, Jia; Yang, Yang; Yiqun, Yan (Frontiers in Energy Research, 2024)
Reservoir numerical simulation is an important tool and method for the reasonable and efficient development of shale reservoirs. Accurate description of three-dimensional fractures in shale reservoir development is a necessary and sufficient condition to improve the accuracy and robustness of shale reservoir numerical simulation. This paper achieves precise characterization of complex fracture shapes and oil, gas and water flow by establishing an embedded discrete fracture model based on a non-structural network, which has advantages in the fine characterization of complex morphological fractures in the reservoir and the grid division of the reservoir. In the large matrix solution method, the Newton-Raphson method is used to linearize the nonlinear equations, the Jacobian matrix is constructed, the ILU method is used for preprocessing, the conjugate gradient method is used to solve the linear equations, and the shale oil quasi-elasticity is established A fully implicit solution method for mathematical models of energy development.shale oil, quasi-elastic energy development, complex fracture modeling, fully implicit solution, numerical simulation 1 Introduction China's continental shale formations are rich in huge shale oil resource potential, with diverse lithofacies, frequent phase changes, developed bedding fractures, and strong heterogeneity. In view of the characteristics of shale oil reservoirs with low permeability and low porosity, which are difficult to be exploited through conventional development methods, hydraulic fracturing is usually used to reform the reservoir first and then develop it. Therefore, for shale oil reservoirs, whether they are artificial fractures or natural fractures, the development of fractures has become a key technical issue. Naturally, in recent years, domestic and foreign scholars have focused their research on the laws and mechanisms of crack development and expansion (Meng, X. B., et al., 2024). Hou Bing et al. conducted an indoor true triaxial indoor fracturing physical simulation experiment and used concrete to wrap a full-diameter downhole core to test the initiation and vertical extension of hydraulic fractures in a